The role of the anterolateral structures and the ACL in controlling laxity of the intact and ACL-deficient knee - Kittl,C; El-Daou,H; Athwal,KK; Gupte,CM; Weiler,A; Williams,A; Amis,AA (AMERICAN JOURNAL OF SPORTS MEDICINE, 2016)
Background:Anterolateral rotatory instability (ALRI) may result from combined anterior cruciate ligament (ACL) and lateral extra-articular lesions, but the roles of the anterolateral structures remain controversial.Purpose:To determine the contribution of each anterolateral structure and the ACL in restraining simulated clinical laxity in both the intact and ACL-deficient knee.Study Design:Controlled laboratory study.Methods:A total of 16 knees were tested using a 6 degrees of freedom robot with a universal force-moment sensor. The system automatically defined the path of unloaded flexion/extension. At different flexion angles, anterior-posterior, internal-external, and internal rotational laxity in response to a simulated pivot shift were tested. Eight ACL-intact and 8 ACL-deficient knees were tested. The kinematics of the intact/deficient knee was replayed after transecting/resecting each structure of interest; therefore, the decrease in force/torque reflected the contribution of the transected/resected structure in restraining laxity. Data were analyzed using repeated-measures analyses of variance and paired t tests.Results:For anterior translation, the intact ACL was clearly the primary restraint. The iliotibial tract (ITT) resisted 31% ± 6% of the drawer force with the ACL cut at 30° of flexion; the anterolateral ligament (ALL) and anterolateral capsule resisted 4%. For internal rotation, the superficial layer of the ITT significantly restrained internal rotation at higher flexion angles: 56% ± 20% and 56% ± 16% at 90° for the ACL-intact and ACL-deficient groups, respectively. The deep layer of the ITT restrained internal rotation at lower flexion angles, with 26% ± 9% and 33% ± 12% at 30° for the ACL-intact and ACL-deficient groups, respectively. The other anterolateral structures provided no significant contribution. During the pivot-shift test, the ITT provided 72% ± 14% of the restraint at 45° for th